Risk factors and clinical characteristics of early-onset colorectal cancer vs. late-onset colorectal cancer: a case-case study. Issue 9 (September 2021) - Di Leo, Milena; Zuppardo, Raffaella A.; Puzzono, Marta; Ditonno, Ilaria; Mannucci, Alessandro; Antoci, Graziana; Russo Raucci, Annalisa; Patricelli, Maria G.; Elmore, Ugo; Tamburini, Andrea M.; Albarello, Luca; Azzolini, Francesco; et al.
Abstract : Background and objectives: Early-onset colorectal cancer (eoCRC), defined as colorectal cancer (CRC) before the age of 50 is increasing in incidence. We evaluated exogenous and endogenous risk factors, and clinical features of eoCRC, compared to late-onset CRC (loCRC). Methods: In this retrospective case-case study, patients were prospectively enrolled from 2015 to 2018. We collected clinical features (age, sex, time from symptom onset to diagnosis, symptoms, family history, smoking and alcohol habits, diabetes, BMI, and genetic analysis) and tumor characteristics. Independent risk factors for eoCRC and odds ratios (ORs) were identified. Results: Fifty-four eoCRCs and 494 loCRCs were enrolled. Patients with eoCRC experienced longer delay time from symptom onset to diagnosis: 40.7% were diagnosed within 6 months from symptoms onset, compared to 85.6% of patients with loCRC ( P < 0.0001). They differed for sex, presence of symptoms, family history, smoking habit, alcohol intake, and BMI. Rectal localization was more closely associated with eoCRC (64.8%) than loCRC (34.5%, P < 0.0001). Family history of CRC was associated with eoCRC (OR = 8.8). When family history occurred with hereditary cancer syndromes, the OR for eoCRC increased to 21. Conclusion: In young adults with alarming symptoms, CRC must be suspected to avoid delay time from symptom onset to diagnosis and genetic risk assessment has to be evaluated. Smoking habits, alcohol intake, and BMI are not associated with eoCRC.